Interacting enzyme systems at steady state: further Monte Carlo calculations on two-state molecules. - Hill, T L (1978)
In this work, Monte Carlo calculations were made on a 10 x 10 lattice of two-state, steady-state enzyme molecules in two special cases for which the Bragg-Williams (mean field) approximation had earlier produced some very interesting phase-transition properties. The Monte Carlo results proved to be similar to Bragg-Williams in some respects but not in others. The discrepancies are attributed primarily to; (i) inadequate treatment by Bragg-Williams of strong negative cooperativity; and (ii) the finite size of the 10 x 10 lattice used in the exact calculations.